AB0096 Two cases of behcet's disease with ulcers on glans penis. (1st June 2001) - Pirildar, T; Turk, T; Tunc, E; Inal, V; Keser, G; Varol, A; Doganavsargil, E; Gumusdis, G
Abstract : Background: Behcet's Disease (BD), when first described in 1937, was consisted of three symptoms; recurrent oral, genital ulcerations and iridocyclitis. Today, it is known that BD is a multisystemic chronic vasculitic disorder which may involve both arteries and veins of all sizes. Although painful scrotal ulcers healing with scar formation are among the main clinical findings of BD, ulceration of glans penis is unusual. Objectives: Methods: Results: We present two cases of BD with ulcers on glans penis. The first case is a 46-year-old man who presented with ulceration involving glans penis and diagnosed as BD after investigations. The second case was a 23-year-old man with established BD who later developed ulcers on glans penis during the course of the disease. In our 113 patients with BD, 102 patients (90.2%) had genital ulcers. Among these 102 patients having genital ulcers, only these two cases (1.9%) had ulcers localised on the glans penis. Conclusion: In conclusion, the possibility of BD should also be considered in patients presenting with genital ulcer (s) with atypical localizations, such as glans penis, particularly in countries with a high prevalance of this disease.